Pituitary Apoplexy with raised intracranial pressure - Pokhrel, Bibesh; Thapa, Amit (Nepal Journal of Neuroscience, 2020)
Pituitary apoplexy in pre-existing pituitary adenomas occurs as a consequence of acute hemorrhage or infarction. Patients with pituitary apoplexy present with sudden onset headache, vomiting, clouding of consciousness and visual field defects or total oculomotor palsies without any prior diagnosis of pituitary tumor.In this case report, we report a case of 52 years female who presented to the emergency department with headache throughout her head and periorbital area with vomiting. Investigations revealed sellar cystic lesion suggestive of pituitary apoplexy with normal hormonal profile. She underwent endoscopic trans-nasal trans-sphenoidal surgery with complete resection of pituitary adenoma. Histopathological examination of tumor specimen showed large areas of necrosis with blood surrounded by the adenomatous tissue. Post-operatively she had cerebrospinal fluid rhinorrhea with persistent papilledema and hydrocephalus. Sellar floor repair along with theco-peritoneal shunt lead to good recovery.